Facilities management of sport complex facilities in public universities / Najdah Muhammad - Muhammad, Najdah (Faculty of Architecture, Planning and Surveying, 2010)
Nowadays, facilities management plays an important role in all types of building in Malaysia. It become importance for building that have provided many types of facilities especially the sport complex to ensure the building users can use and work comfortable and safety. For this reason, it should have a good maintenance services to sustain the function of all facilities in building whereby it will fulfill building users need. The effectiveness of the aspects of maintenance such as strategies, planning and procedure and organization management will maintain the building quality performance all the times. In order to determine the maintenance aspects in facilities management, 3 case studies was conducted on Sport Complex UiTM, Sport Complex UKM and Sport Complex UPM. The data was collected via interview with person who involved in maintenance management. Based on the case studies, it found that the maintenance aspect in facilities management of Sport Complex consist of planning, maintenance work system and scheduling of work. In this study, several improvements to existing building maintenance management especially from the aspect that facilities provided and the maintenance management in this case studies have been identified. So, it can be a guideline for an effective facilities and maintenance management.